Development of a healthcare building sustainability assessment method - Proposed structure and system of weights for the Portuguese context - Castro, M. F. (2017)
In healthcare building projects, it is necessary to consider a larger number of different aspects than in other building types, as patients' emotions, comfort needs and the integration of latest technologies. To design these buildings, considering a sustainable approach, the sustainable practices for healthcare building should be considered properly in design and use phases. Therefore, there is a lack of common understanding on the field of various relations between built, natural and social systems. To tackle this, the goal of this article is to contribute to the better understanding in this context by exposing a proposal for the structure and system of weights of the sustainability criteria of a healthcare building sustainability assessment method, the HBSAtool-PT. The methodological approach adopted is innovative since in the development of the list of sustainability criteria it considers the opinion of main healthcare buildings? stakeholders, the existing healthcare assessment methods and the ISO and CEN standardisation works in the field of the methods to assess the sustainability of construction works. Additionally, a methodology to develop the weighting system to be used in the aggregation of the different indicators is proposed and applied to the Portuguese context. As a result, the proposed sustainability assessment system for healthcare buildings (HBSAtool-PT) embraces fifty-two sustainability indicators that cover the different dimensions of the sustainability concept to support decision making during the design of a new or retrofitted healthcare building in urban areas. The proposed structure for the HBSAtool-PT presents a more balanced structure between the dimensions of the sustainable development, and compared with other existing approaches, it integrates more comprehensive social and economic concerns.